Cultivation and Production of Agaricus bisporus in Zaccar (Algeria) - Guetarni, Hassina (Mushroom Research, 2022)
Mushroom production is very well suited to sustainable agriculture. Mushrooms provide additional protein, essential vitamins and minerals. The objective of this work is to promote, from the culture of Agaricus bisporus, the development of the mycelium. The product obtained at the end of this operation is called "white mother" which will be used later to inoculate the fruiting substrate which is based on horse manure and straw. From the kits, pure cultures of mycelium were produced on Potato dextrose agar medium, which were then inoculated into various sowing substrates under strict aseptic conditions. The results obtained show that the cultivated fungus is sensitive to various fungal pathogens.